Can Lebanon's economy be saved? A plan for revival - Dagher, Leila (2021)
The recent financial and economic meltdown in Lebanon is the result of 30 years of social, economic, financial, and fiscal mismanagement, amplified by the Covid-19 pandemic and further exacerbated by the Beirut port explosion. Lebanese citizens’ trust, as well as the international community's trust in the government, have unfortunately been destroyed. Consequently, Lebanon's sole option is to rebuild confidence in the government and public institutions by implementing economic reforms and to seek an IMF program to pave the way for additional financing from other international sources. The most important confidence-building step is a clear financial and economic plan that has the support of all key stakeholders. This article presents a road map for a reforms-driven, export-led growth strategy for Lebanon. Ultimately, the goal is to jump-start the economy and put it on a path of sustainable, inclusive, and equitable economic growth. Such growth should be grounded in a small, open-economy model and driven by low tariffs, a flexible exchange rate regime, and a dynamic export sector built on competitive and comparative advantages. This plan partially builds on proposals and recommendations provided by previous economic plans and policy notes.